Repeatability of Microperimetry in Areas of Retinal Pigment Epithelium and Photoreceptor Loss in Geographic Atrophy Supported by Artificial Intelligence–Based Optical Coherence Tomography Biomarker Quantification - Coulibaly, Leonard M.; Birner, Klaudia; Zarghami, Azin; Gumpinger, Markus; Schürer-Waldheim, Simon; Fuchs, Philipp; Bogunović, Hrvoje; Schmidt-Erfurth, Ursula; Reiter, Gregor S. (American journal of ophthalmology, 2025)
Growing interest in microperimetry (MP) or fundus-controlled perimetry as a targeted psychometric testing method in geographic atrophy (GA) is warranted because of the disease subclinical/extrafoveal appearance or preexisting foveal loss with visual acuity becoming unreliable. We provide comprehensive pointwise test-retest repeatability reference values on the most widely used MP devices and combine them with targeted testing in areas of retinal pigment epithelium (RPE) as well as photoreceptor (PR) integrity loss, guiding the interpretation of sensitivity loss during the long-term follow-up of patients with GA. Prospective reliability study. Patients with GA underwent consecutive testing on CenterVue (iCare) MAIA and NIDEK MP3 devices. Obtained pointwise sensitivity (PWS) measurements were spatially coregistered to an optical coherence tomography volume scan acquired during the same visit. Areas with RPE and PR integrity loss, drusen, and PR thickness as well as the volume of hyperreflective foci where identified and quantified using a set of validated deep learning–based algorithms. Test-retest repeatability was assessed according to areas defined by biomarker-specific morphologic changes using Bland-Altmann coefficients of repeatability. Furthermore, the interdevice correlation, the repeatability of scotoma point detection, and any potential effects on fixation stability were assessed. Nine hundred stimuli per device from 20 subjects were included. Identical overall PWS test-retest variance could be detected for MAIA (±6.57) and MP3 (±6.59). PR integrity loss was associated with a higher test-retest variance on both devices (MAIA, P = .002; MP3, P < .001). Higher coefficients of repeatability for stimuli in areas presenting RPE loss (±10.99 vs ±5.34) or hyperreflective foci (±9.21 vs ±6.25) could only be detected on MP3 examinations (P < .001 and P = .01, respectively). An excellent intradevice correlation (MAIA 0.94 [0.93-0.95], MP3 0.94 [0.94-0.95]) and a good mean interdevice correlation (0.84 [0.53-0.92]) were demonstrated. The chosen device, run order, or absence of foveal sparing had no significant effect on fixation stability. Areas presenting automatically quantified PR integrity loss with and without underlying RPE loss are associated with higher test-retest variance for both MAIA and MP3. These findings are crucial for an accurate interpretation of GA progression during long-term follow-up and the planning of future trials with MP testing as functional study endpoint.